Complete design of an efficient and fully integrated graphene-based compact plasmon coupler for the infrared - Renversez Gilles; Natarajan Aswani; Demésy Guillaume (EPJ Web of Conferences, 2023)
A fully integrated waveguide-based, efficient surface plasmon coupler composed of a realistic nontapered dielectric waveguide with graphene patches and sheet is designed and optimized for the infrared. The coupling efficiency can reach nearly 80% for an optimized coupler as short as 700 nm for an operating wavelength of 12µm. This work is carried out using rigorous numerical models based on the finite element method taking into account 2D materials as surface conductivities and the finite number of graphene patches contrarily to the usual methods based on grating analysis. The key numerical results are supported by physical arguments based on a modal approach or resonance conditions. These arguments can help to design other similar couplers or tofind the optimized parameters at other wavelengths.